2024
DOI: 10.1177/03331024241245658
|View full text |Cite
|
Sign up to set email alerts
|

Medication “underuse” headache

Wanakorn Rattanawong,
Alan Rapoport,
Anan Srikiatkhachorn

Abstract: Background Many risk factors have been associated with migraine progression, including insufficient and ineffective utilization of migraine medications; however, they have been inadequately explored. This has resulted in suboptimal usage of medications without effective altering of prescribing recommendations for patients, posing a risk for migraine chronification. Methods Our aim is to conduct a comprehensive review of the available evidence regarding the underuse of migraine medications, both acute and preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…Traditional migraine preventive trial targets of a 50% reduction in attack frequency help assess an intervention versus a comparator, but may not imply meaningful improvement in quality of life. As Rattanawong et al point out, increasing evidence suggests that headache begets headache (1,2). This implies that the more time the brain spends in a migraine-on state, or walking the migraine path, as we explain to patients, the more easily activated that pathway can become until eventually the path becomes a highway.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Traditional migraine preventive trial targets of a 50% reduction in attack frequency help assess an intervention versus a comparator, but may not imply meaningful improvement in quality of life. As Rattanawong et al point out, increasing evidence suggests that headache begets headache (1,2). This implies that the more time the brain spends in a migraine-on state, or walking the migraine path, as we explain to patients, the more easily activated that pathway can become until eventually the path becomes a highway.…”
mentioning
confidence: 75%
“…Despite advances in migraine-targeted therapies, some patients have not yet been helped by available options. As Rattanawong et al note, patients with a suboptimal response to acute therapy are at higher risk of migraine progression (1,8), and one study found that patients with an inadequate response to triptans had higher headache frequency than triptan responders (9). However, we do not know whether differences in acute medication responsiveness reflect differences in disease process.…”
mentioning
confidence: 82%
See 1 more Smart Citation